PENGARUH WORK LIFE BALANCE DAN MOTIVASI TERHADAP LOYALITAS KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT SIMS JAYA KALTIM - Suyudi, Akhmad; Khan, Ryan Basith Fasih (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the effect of work life balance and work motivation on employee loyalty with job satisfaction as a mediating variable at PT SIMS Jaya Kaltim, involving all company employees with a sample of 194 respondents. Human resources (HR) have an important role in determining the progress of a company. Employee loyalty is one indicator of superior HR quality, which is influenced by work life balance, work motivation, and job satisfaction. The results showed that work life balance has a positive and significant effect on job satisfaction and employee loyalty. Work motivation also has a positive and significant influence on job satisfaction and loyalty. In addition, work life balance and work motivation are proven to influence employee loyalty through job satisfaction as a mediating variable. This research confirms that work-life balance, as well as the provision of appropriate work motivation, is very important in increasing employee satisfaction and loyalty, which in turn can support the progress of the company.